Capgermacrene C, a New Sesquiterpenoid from a Bornean Soft Coral, Capnella sp. - Takahiro, Ishii; Charles Santhanaraju Vairappan; Chin, Soon Phan; Takashi Kamada (Natural Product Communications, 2016)
A new bicyclogermacrene, capgermacrene C (1), along with a known compound, 1,4-peroxy-5-muurolene (2), were isolated from a population of Bornean soft coral Capnella sp. The structures of these metabolites were determined by extensive spectroscopic analysis, including NMR, and HRESIMS. Both compounds were subjected to antibacterial activity tests against antibiotic resistant clinical bacteria, but produced only negligible inhibition.